Evolution and structure of magnetic fields in simulated galaxy clusters - Dolag, Klaus; Bartelmann, Matthias; Lesch, Harald (Astronomy and astrophysics, 2002)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics